2013
DOI: 10.1177/0192623313501235
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Carcinogenicity Studies of Ginkgo biloba Extract in Rat and Mouse

Abstract: Ginkgo biloba extract (GBE) is a popular herbal supplement that is used to improve circulation and brain function. In spite of widespread human exposure to relatively high doses over potentially long periods of time, there is a paucity of data from animal studies regarding the toxicity and carcinogenicity associated with GBE. In order to fill this knowledge gap, three-month and two-year toxicity and carcinogenicity studies with GBE administered by oral gavage to B6C3F1/N mice and F344/N rats were performed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…The study was performed by NIH National Toxicology Program (NTP) and concluded that GBE might elicit toxic and cancer-related consequences in rodents. The carcinogenic effects reported were stomach ulcers, organ modification including carcinogenic activity in the liver, liver and thyroid gland hypertrophy, liver hyperplasia, and hyperkeratosis (National Toxicology Program, 2013;Rider et al, 2014). These reports raised concerns about the safety of GBE.…”
Section: Safety Toxicity and Side Effects Of G Bilobamentioning
confidence: 99%
“…The study was performed by NIH National Toxicology Program (NTP) and concluded that GBE might elicit toxic and cancer-related consequences in rodents. The carcinogenic effects reported were stomach ulcers, organ modification including carcinogenic activity in the liver, liver and thyroid gland hypertrophy, liver hyperplasia, and hyperkeratosis (National Toxicology Program, 2013;Rider et al, 2014). These reports raised concerns about the safety of GBE.…”
Section: Safety Toxicity and Side Effects Of G Bilobamentioning
confidence: 99%
“…Although a human study demonstrated that GBE may protect from oxidative and genotoxic damage due to treatment with radioactive iodine in thyroid cancer patients (Dardano et al, 2012), GBE was classified as being possibly carcinogenic to humans (2B group) by the International Agency for Research on Cancer (IARC, 2016).The results of animal studies demonstrated that GBE could induce pathological changes in the hepatic, thyroid, and nasal tissues of mice and rats. The most obvious carcinogenic responses were the increase in liver tumors in mice and thyroid gland follicular cell tumors in rats (Rider et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments of GBE mainly focused on demonstrating its anticarcinogenic and antioxidant properties without paying attention to its possible toxicity and carcinogenicity (Mahadevan and Park 2008). However, a recent study demonstrated that oral GBE intake resulted in increase in liver tumors in male and female mice and thyroid gland follicular cell tumors in male and female rats (Rider et al, 2014).…”
mentioning
confidence: 99%
“…Raised incidences of hyaline droplet accumulation and olfactory epithelium pigmentation were also found. 11 These studies provide substantial evidence on how Ginkgo biloba can produce cancerous lesions but reports of any such events are required in human subjects also for conclusive validation.…”
Section: Ginkgo Bilobamentioning
confidence: 99%